PERANCANGAN SISTEM INFORMASI PENJUALAN BUKET DAN KADO PADA TOKO UKIII BEEFLORIST BERBASIS WEB DENGAN METODE WATERFALL: PERANCANGAN SISTEM INFORMASI PENJUALAN BUKET DAN KADO PADA TOKO UKIII BEEFLORIST BERBASIS WEB DENGAN METODE WATERFALL - Gladis (Himpunan Dosen Ilmu Komputer, 2023)
Toko Ukiii Beeflorist is a business that offers a variety of bouquet and gift products. It is located on Jalan Raya, Jeriji Village, specifically in Toboali District, South Bangka Regency, Bangka Belitung Islands. Currently, the marketing system employed by Toko Ukiii Beeflorist is not effective. The delivery of information regarding product details, such as prices and stock items, is also minimal, resulting in a slow service process. To improve data management, a website-based information communication technology system should be designed and implemented. This will lead to more effective information, improved marketing, and better customer support services. The system should be designed and developed using the waterfall method, and analyzed using system modeling with UML. The study presents a system design customized to meet the requirements of the Ukiii Beeflorist Shop. This design can aid in the development of an efficient and precise information system for data and information management.